NEFROTOKSISITAS OBAT KEMOTERAPI BERBASIS CISPLATIN PADA PASIEN KANKER PARU JENIS NON-SMALL CELL LUNG CANCER DI RUMAH SAKIT KANKER DHARMAIS TAHUN 2018 - Taufik Ramdani (2020)
Lung cancer is an abnormal and uncontrolled growth of the lung cells. One of the therapy that could be given is chemotherapy using cisplatin. This chemotherapy has a side effect of nephrotoxicity. Nephrotoxicity can be seen from the elevation of serum creatinine and the reduction of eGFR before and after chemotherapy. This research was done to find out the effects of nephrotoxicity from cisplatin-based chemotherapy on lung cancer patients type NSCLC at Dharmais Cancer Hospital 2018. This is an observational analytic study with cross-sectional design using secondary data from medical records. The sampling was done with total sampling and got a total of 36 patients. Friedman test was used as a data analysis on the serum creatinine data and Repeated ANOVA test was used for the eGFR data. The result stated that most of the patients are >40 years old (83,3%) in which most of them are male (66,7%), most of the types adenocarcinomas (83,3%) and chemotherapy regimen that was most used is the cisplatin-pemetrexed (61,1%). The comparison result showed that there is a significant difference between the average serum creatinine p= 0,000 (p<0,05) and the average eGFR p= 0,000 (p<0,05) before chemotherapy and after chemotherapy I and II. This research showed that there's yet to be any effect of nephrotoxicity based on the elevation of serum creatinine levels (0,235 mg/dL) and that there is an effect of nephrotoxicity based on the reduction of the eGFR levels (80,22ml/min/1,73m2).